CRITICAL SUCCESS FACTOR FOR IMPLEMENTING KM IN GOVERNMENT HUMAN CAPITAL MANAGEMENT: CASE STUDY BADAN KEPEGAWAIAN NEGARA - Elin Cahyaningsih; Dana Indra Sensuse (Faculty of Computer Science Universitas Indonesia, 2014)
Abstract Nowadays, knowledge management in organization became a trend strategy in order to improve organization performance. But unfortunately, it’s a big challenge to implementing knowledge management in organization, because it’s relatively new and not many people knew about this. This research is done in order to realize bureaucratic reform in government service improvement according to PERMENPAN No. 14 Tahun 2011 is about knowledge management (KM) implementation in government. Knowledge management cannot be separated from human capital as an intangible asset in organization which has an important role to the success of organization goals. This conducted research aims to identify critical success factor of KM implementation in Indonesian government human capital management case study: Badan Kepegawaian Negara. Stages of this research are literature study, data collection using interviews, observation, and group discussion organization to explore and discovering critical success factor for KM implementation. Data analysis using descriptive statistic, delphi method and expert judgment in order to define critical success factor of implementing KM in government human capital management: case study in Badan Kepegawaian Negara. The result shows that several critical success factors for KM implementation in the government human capital management are organization culture, leadership, organization structure, HR/HC (knowledge, skill, attitude), HR/HC process (acquisition, development, engagement, retention) and policy.